Glass ceiling pada Jurnalis Perempuan di Newsroom Media Online - Silaban, Martha Warta; Septiana, Rizka (Jurnal InterAct, 2020)
The arrival of the internet has no doubt affected the media business. As of now, the amount of online media outnumbers print media. However, the presence of female journalists across online media newsrooms has not shown significance, especially in decision-making levels. This study examines female journalists working in online media. The glass ceiling theory is used in this study and coupled with the concept of jender and organizational communication. Phenomenology will be the methodology used to examine the journalists’ experience to reach the editorial leader level, editor, or assistant editor. The result of this study also showcases that media outlets with an equal amount of female and male journalists will have equal reporting duties and script editing regardless of jender. The tasks are adjusted to work schedules even with jender- related training programs given to anyone. Meanwhile, media outlets with more male journalists compared to female counterparts provide greater chances for male workers to reach the top level. Despite not annulling the chances for female journalists to reach decision-making levels. Female journalists who succeed in breaching this glass ceiling can do it by showing exceptional work performances. Female employees must be able to penetrate the patriarchal culture that still exists in several Indonesian media because the existence of female journalists provides balanced coverage regarding women.